Conocimiento y actitud hacia medidas de prevención del COVID-19 de la junta vecinal José Smith del pueblo joven Tupac Amaru Iquitos 2023 - Ruiz Padilla, Karla Sunamita (2024)
The objective was to determine the relationship that exists between the knowledge and attitude towards COVID-19 prevention measures in residents of the José Smith Neighborhood Council of the Pueblo Joven Tupac Amaru Iquitos 2023. The method was quantitative and the design was non experimental. correlational descriptive. The population and sample were made up of 150 people from the Neighborhood Council of the young town José Smith Tupac Amaru Iquitos 2023. The technique was the survey and the instruments were the Knowledge Questionnaire on COVID-19 prevention measures and the Likert Scale to evaluate attitude. towards COVID-19 prevention measures. For data processing, the SPSS statistical package version 24.0 was used and for the correlational analysis the chi square statistical test (2), considering a significance level of 95% with alpha α = 0.05. The results were: For the level of knowledge about COVID-19 prevention measures, 90.9% of the residents demonstrated a low level of knowledge while the remaining 9.1% demonstrated a high level. Likewise, for the type of attitude towards COVID 19 prevention measures, 88.9% presented a negative attitude and the remaining 11.1% a positive attitude. In conclusion, it was shown that there is a statistically significant association (p= 0.018 (p < 0.05)) between the level of knowledge and the type of attitude towards COVID-19 prevention measures.